2018
DOI: 10.1038/s41598-018-21101-w
|View full text |Cite
|
Sign up to set email alerts
|

The wavelength of the incident light determines the primary charge separation pathway in Photosystem II

Abstract: Charge separation is a key component of the reactions cascade of photosynthesis, by which solar energy is converted to chemical energy. From this photochemical reaction, two radicals of opposite charge are formed, a highly reducing anion and a highly oxidising cation. We have previously proposed that the cation after far-red light excitation is located on a component different from PD1, which is the location of the primary electron hole after visible light excitation. Here, we attempt to provide further insigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…Our results are also in very good agreement with the suggestion that Y Z becomes the preferred electron donor under far-red light at 5 K. The migration of the Chl D1 hole to the special pair would require a reorganization of the protein environment that is probably inhibited at cryogenic temperature, resulting in Y Z becoming an electron donor to Chl D1 . Further EPR experiments 39 showed that charge separation upon light excitation is wavelength-dependent, leading to the hypothesis that P D1 is excited with visible light (532 nm), whereas Chl D1 is excited with far-red light. 39 Our results on the P D1 –P D2 –Chl D1 trimer do not support the presence of any energetically accessible CT state that could lead directly to productive charge separation along the D1 branch, but the conditions under which the special pair may function as the primary donor will need further studies to be clarified.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results are also in very good agreement with the suggestion that Y Z becomes the preferred electron donor under far-red light at 5 K. The migration of the Chl D1 hole to the special pair would require a reorganization of the protein environment that is probably inhibited at cryogenic temperature, resulting in Y Z becoming an electron donor to Chl D1 . Further EPR experiments 39 showed that charge separation upon light excitation is wavelength-dependent, leading to the hypothesis that P D1 is excited with visible light (532 nm), whereas Chl D1 is excited with far-red light. 39 Our results on the P D1 –P D2 –Chl D1 trimer do not support the presence of any energetically accessible CT state that could lead directly to productive charge separation along the D1 branch, but the conditions under which the special pair may function as the primary donor will need further studies to be clarified.…”
Section: Resultsmentioning
confidence: 99%
“…Further EPR experiments 39 showed that charge separation upon light excitation is wavelength-dependent, leading to the hypothesis that P D1 is excited with visible light (532 nm), whereas Chl D1 is excited with far-red light. 39 Our results on the P D1 –P D2 –Chl D1 trimer do not support the presence of any energetically accessible CT state that could lead directly to productive charge separation along the D1 branch, but the conditions under which the special pair may function as the primary donor will need further studies to be clarified.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2). Many photons are beyond 680 nm, wavelengths that are not used or used far less efficiently by PSII, because the primary donor of PSII (P 680 ) is not formed (Pavlou et al 2018). As a result, red light could cause an imbalance in photosynthetic electron transport.…”
Section: Phycoerythrin Concentrationmentioning
confidence: 99%
“…One of the two CT pathways may be favored due to the specific conformation of the protein ( 7 ) or the wavelength of incident light ( 8 ). Vibronic coupling between states has been identified ( 9 ), which facilitates switching between the two available pathways ( 10 ) to further assist efficient CS.…”
mentioning
confidence: 99%